(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
As a powerful driver of economic development, tourism is paramount in nations rich in natural and cultural assets. This study undertakes a nuanced exploration of the dynamic interplay between tourism and economic growth within the unique context of Nepal. Against the backdrop of Nepal’s evolving tourism landscape, this research aims to untangle the multifaceted impacts of tourism on the nation’s economic indicators. The study adopts a comprehensive approach, utilizing diverse methods for data acquisition. A judiciously selected sample serves as the cornerstone for analysis. The results are systematically presented and organized around key research questions and thematic areas. To enhance clarity, the presentation of findings is augmented by a judicious use of visual aids such as tables, charts, and graphs. The discussion segment meticulously interprets these results within the context of the research questions, drawing insightful comparisons with existing literature and pertinent previous studies. The practical implications of the findings for Nepal’s tourism industry take centre stage. In addition to presenting critical insights, the paper provides detailed policy recommendations to enhance tourism infrastructure and services. It outlines strategies for promoting sustainable tourism practices and underscores the importance of community involvement and cultural preservation. This study recapitulates its objectives and key findings and accentuates its broader contributions to tourism and sustainable development. Acknowledging its limitations, the paper suggests avenues for future research, encouraging an ongoing exploration of leveraging tourism as a catalyst for economic growth in Nepal. The research is a valuable resource, offering nuanced insights into the potential of sustainable tourism practices and community engagement in fostering robust economic development within the Nepalese context.